Reading Micaiah’s heavenly vision (1 Kgs 22:19–23) and 1 Kings 22 as interpretive keys - Quine, Cat (De Gruyter, 2018)
This paper argues that Micaiah’s heavenly vision (1Kgs 22:19–23) and 1Kgs 22 as a whole function as interpretive keys which explain subsequent material to the reader. Micaiah’s heavenly vision explains that the following Aramean victory and the death of the king of Israel (1Kgs 22:29–36) did not present a challenge to Yahweh’s supreme authority, but rather confirmed it. On a broader scale, 1Kgs 22 combined themes and events from the material around it (1Kgs 16–21; 2Kgs 3–13) to create a narrative that explained the historical events of the rise of the Arameans and the downfall of the Omrides. The chapter uses Ahab and Jehoshaphat as representatives of the kings of Israel and Judah to tell a story which explained how Yahweh used the Arameans to bring about the fall of the Omrides and free Judah from Israelite control.